1992
DOI: 10.1152/ajpheart.1992.263.4.h1095
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of structure and viscoelastic properties in the pericardia of four mammalian species

Abstract: Although the pericardium is recognized as having important contributions to ventricular function, the relationship between its functional role and structural composition remains poorly understood. Conflicting evidence from low strain rate experiments has shown that differences exist between the mechanical properties of canine, human, and bovine pericardium but with no structural explanation for these differences. This paper examines the pericardia of calves, dogs, pigs, and sheep using a structural/mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 18 publications
1
35
1
Order By: Relevance
“…By contrast, the increased strain at fracture for the HMDC group may be explained by increased collagen crimp after crosslinking which subsequently collapses under high stress levels [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This observation is consistent with the dimensional shrinkage seen in glutaraldehyde crosslinking by Trowbridge and co-workers and calculated by Lee et al [31,18].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…By contrast, the increased strain at fracture for the HMDC group may be explained by increased collagen crimp after crosslinking which subsequently collapses under high stress levels [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This observation is consistent with the dimensional shrinkage seen in glutaraldehyde crosslinking by Trowbridge and co-workers and calculated by Lee et al [31,18].…”
supporting
confidence: 82%
“…Initially, there is a decrease in load due to stress relaxation. Eventually, the temperature of the bath provides enough energy to break hydrogen bonds which stabilize the highly ordered helical structure of this predominantly collagenous material [18]. This results in a conformational change into a random coil configuration which would produce observable shrinkage of the tissue were it unconstrained; however, since the tissue is held at a fixed extension (isometric constraint), the point at which the tissue denatures is registered as a sharp increase in the force exerted on the tissue strip.…”
Section: Denaturation Temperature Testsmentioning
confidence: 99%
“…Similarly, Naimark et al (Naimark et al, 1992) showed no significant strain rate dependence in the stress-strain relationship of mammalian pericardia for strain rates between 1 and 100%/s. The authors speculated strain rate insensitivity may be attributed to the stabilizing effects of glycosaminoglycans that surround the pericardial collagen fibers.…”
Section: -3) (Grashow Et Al 2006bmentioning
confidence: 93%
“…The contribution of collagen type I can be estimated as 71.8 š 2.1% (dry weight). 21 Three 15 ð 10 mm rectangles were excised from each pericardium.…”
Section: Experimental Materialsmentioning
confidence: 99%